2013
DOI: 10.7750/biodiscovery.2013.7.1
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome rearrangements in sublines of human embryonic stem cell lines hESM01 and hESM03

Abstract: Due to possible proliferative effects of karyotypic reorganization of human embryonic stem cell (hESC) lines detailed genetic analysis are indicated prior to any application of hESCs. Molecular cytogenetic analysis of two different hESC sublines was performed and revealed aberrant chromosomes in both of them, i.e. in hESM01r18 (46,ХХ,-18,+mar) and hESM0309 (46,ХХ,del(4),dup (9)). This study shows that microdissection and multicolor fl uorescence in situ hybridization (mFISH) can be used to detect the chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“… 21 did not find r(17) in iPSC metaphases may be associated with the localization of the antiapoptotic BIRC5 gene, which provides a proliferative advantage, in the 17q25 region 48 , 49 such that ring instability or monosomy 17 may compromise the ability of pluripotent cells to divide more strongly than for other rings (r(13), r(18), and r(22)). Ring chromosome 18, which appeared in the ESC subline hESM01r18, was also quite stable 50 . The size of the chromosome.…”
Section: Discussionmentioning
confidence: 98%
“… 21 did not find r(17) in iPSC metaphases may be associated with the localization of the antiapoptotic BIRC5 gene, which provides a proliferative advantage, in the 17q25 region 48 , 49 such that ring instability or monosomy 17 may compromise the ability of pluripotent cells to divide more strongly than for other rings (r(13), r(18), and r(22)). Ring chromosome 18, which appeared in the ESC subline hESM01r18, was also quite stable 50 . The size of the chromosome.…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that hESCs should be molecular cytogenetically characterised in an attempt to understand tumour initiation and progression. [31]. Likewise, incomplete reprogramming of hiPSCs from somatic cells is an additional hurdle.…”
Section: Obstacles In the Face Of Stem Cell Technologymentioning
confidence: 99%